Abnormal Glucose Metabolism Parameters and the Aggressiveness of Differentiated Thyroid Carcinoma: A Hospital-Based Cross-Section Study in China - Zhao, Junyu; Tian, Yutian; Jia, Zhen; Yao, Jinming; Liao, Lin; Dong, Jianjun (Frontiers in Endocrinology, 2022)
Purpose: The correlation of abnormal glucose metabolism and thyroid carcinoma, especially the aggressiveness of thyroid cancer, still remains controversial. We conducted this study to investigate the relationship between abnormal glucose metabolism parameters and differentiated thyroid carcinoma (DTC) in Chinese population. Materials and methods: The study was designed as a hospital-based case-control study and approved by the Ethics Committee of our hospital and registered in the Clinical Trial Protocol Registration and Results System (Registration code: NCT 03006289). From January 1, 2018 to June 30, 2021, a total of 377 DTC patients were enrolled in the study. Demographic and general characteristics, details of thyroid surgery and histopathological results, hematological test indicators were collected. Glucose metabolism parameters were calculated. Variables were analyzed by t-test, ANOVA, chi-squared analysis and Fisher's exact test. Pearson bi-variate correlation and Sperman’ s correlation analysis were used for bi-variate analysis. Results: More than 40% of patients with DTC were multifocality, more than half were extra-glandular invasion, and nearly 85% complied by lymph node metastasis. The prevalence of diabetes mellitus (DM) was about 10.08% in DTC patients. It was found that the proportion of postprandial 2h blood glucose ≥ 11.1mmol/ L and HbA1c ≥ 6.5% was significantly higher than the known proportion of DM (17.8%, 16.7% vs. 10.08%). What’s more, 87.3% of the DTC patients in this study had a varying degrees of insulin resistance. Further analysis found that higher T staging was associated with higher levels of area under curve of C-peptide (P=0.029), insulin sensitivity index (P=0.012) and C-peptide sensitivity index (P=0.016). A delayed peak of insulin secretion was found to be positive related with capsule invasion (r=0.206, P=0.004). In patients without a DM history, homeostasis model assessment of insulin resistance (P=0.017), insulin sensitivity index (P=0.019) and C-peptide sensitivity index (P=0.020) were statistic associated with T staging. Also, the glucose metabolism parameter at 3-hour after a meal was related to a larger number of metastatic lymph nodes. Conclusion: Abnormal glucose metabolism, including DM, hyperinsulinemia and insulin resistance, were significantly associated with the carcinogensis and aggressiveness of DTC.